A Monte Carlo study of the effect of an ultrasound transducer on surface dose during intrafraction motion imaging for external beam radiation therapy. Issue 10 (20th August 2017) - Martyn, Michael; O'Shea, Tuathan P.; Harris, Emma; Bamber, Jeffrey; Gilroy, Stephen; Foley, Mark J.
Abstract : Purpose: The aim of this study was to estimate changes in surface dose due to the presence of the Clarity Autoscan™ ultrasound (US) probe during prostate radiotherapy using Monte Carlo (MC) methods. Methods: MC models of the Autoscan US probe were developed using the BEAMnrc/DOSXYZnrc code based on kV and MV CT images. CT datasets were converted to voxelized mass density phantoms using a CT number‐to‐mass density calibration. The dosimetric effect of the probe, in the contact region (an 8 mm × 12 mm single layer of voxels), was investigated using a phantom set‐up mimicking two scenarios (a) a transperineal imaging configuration (radiation beam perpendicular to the central US axial direction), and (b) a transabdominal imaging configuration (radiation beam parallel to the central US axial direction). For scenario (a), the dosimetric effect was evaluated as a function of the probe to inferior radiation field edge distance. Clinically applicable distances from 5 mm separation to 2 mm overlap were determined from the radiotherapy plans of 27 patients receiving Clarity imaging. Overlaps of 3 to 14 (1 to 3 SD) mm were also considered to include the effect of interfraction motion correction. The influence of voxel size on surface dose estimation was investigated. Approved clinical plans from two prostate patients were used to simulate worst‐case dosimetric impact of the probe when large couch translations were applied to correct for interfraction prostate motion. Results: The dosimetric impact of both the MV and kV probe models agreed within ±2% for both beam configurations. For scenario (a) and 1 mm voxel model, the probe gave mean dose increases of 1.2% to 4.6% (of the dose at isocenter) for 5 mm separation to 0 mm overlap in the probe‐phantom contact region, respectively. This increased to 27.5% for the largest interfraction motion correction considered (14 mm overlap). For separations of ≥ 2 mm dose differences were < 2%. Simulated dose perturbations were found to be superficial; for the 14 mm overlap the dose increase reduced to < 3% at 5.0 mm within the phantom. For scenario (b), dose increases due to the probe were < 5% in all cases. The dose increase was underestimated by up to 13% when the voxel size was increased from 1 mm to 3 mm. MC simulated dose to the PTV and OARs for the two clinical plans considered showed good agreement with commercial treatment planning system results (within 2%). Mean dose increases due to the presence of the probe, after the maximum interfraction motion correction, were 16.3% and 8.0%, in the contact region, for plan 1 and plan 2, respectively. Conclusions: The presence of the probe results in superficial dose perturbations for patients with an overlap between the probe and the radiation field present in either the original treatment plan or due to translation of the radiation field to simulate correction of interfraction internal prostate motion.